The distribution and importance of Quiet Areas in the EU. (1st December 2017) - Votsi, Nefta-Eleftheria P.; Kallimanis, Athanasios S.; Pantis, John D.
Graphical abstract: Highlights: QAs of EU were identified at national, environmental and altitudinal level. Mapped QAs were overlaid on Natura 2000 sites. An environmental policy was proposed integrating biodiversity and quietness. The distributional pattern of Quietness is uneven forming a surrogate of urbanism. Abstract: The delineation of Quiet Areas (QAs) forms nowadays a national obligation of EU countries. Nevertheless the variable applications of QAs among Member-States have highlighted the need for an international common approach for the preservation of Quietness. The objective of this paper is to identify and thus protect QAs of EU. Our methodological design consisted of the implementation of a coarse scale distance-based methodology regarding the identification of QAs among different countries, environmental and altitudinal zones with a view to investigating the spatial pattern of QAs as well as their spatial relation to other protected areas. QAs cover 56.09% of EU territory with most of the sites comprising an area larger than 100 km 2 indicating that Quietness provides a valuable ecosystem service for human well-being. Central Europe demonstrates lower percentages of Quietness whereas Mediterranean and Scandinavian areas contain higher percentages of Quietness. Also our findings regarding the spatial overlap of QAs with Natura 2000 network suggest that QAs actually indicate sites of environmental quality, and could thus be incorporated into environmental policy initiatives.